Pengaruh Persepsi Wajib Pajak Atas Pp No. 55 Tahun 2022 Dan Kewajiban Moral Terhadap Kepatuhan Wajib Pajak UMKM - Angelica, Stevania; Khairani, Siti (VALUE, 2025)
This study aims to examine the influence of taxpayers' perceptions of Government Regulation No. 55 of 2022 and moral obligations on the tax compliance of MSME taxpayers. A quantitative approach was employed in this research. The population consists of all MSME taxpayers in Palembang, while the sample comprises 100 MSME taxpayers with a gross turnover of less than IDR 4,800,000,000 in 2023, registered at KPP Pratama Ilir Timur Palembang. The primary data used was collected through respondents' opinions using a Google Form, processed in numerical form. The data was analyzed using statistical tests processed through SPSS software version 26. Several tests conducted include data quality tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and determination coefficient tests. The results of the study conclude that taxpayers' perceptions of Government Regulation No. 55 of 2022 and moral obligations significantly influence MSME taxpayers' compliance. This indicates that the better a taxpayer's understanding of Government Regulation (PP) No. 55 of 2022 and the stronger their moral values, the higher the likelihood of improved compliance with their tax obligations.